2021
DOI: 10.1038/s41598-021-81931-z
|View full text |Cite
|
Sign up to set email alerts
|

A clinical pilot study on the effect of the probiotic Lacticaseibacillus rhamnosus TOM 22.8 strain in women with vaginal dysbiosis

Abstract: Lactobacilli with probiotic features play an essential role in maintaining a balanced vaginal microbiota and their administration has been suggested for the treatment and prevention of vaginal dysbiosis. The present study was aimed to in vitro and in vivo investigate the probiotic potential of the Lacticaseibacillus rhamnosus TOM 22.8 strain, isolated from the vaginal ecosystem of a healthy woman. For this purpose, safety and functional properties were in depth evaluated. The strain exhibited a broad spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Nevertheless, the results should be interpreted cautiously as the number of studies included in the meta-regression analysis was rather limited ( k = 10). Similar to our results, a probiotic administration for a 10-day duration resulted in a significant reduction of pathogenic microbiota in vagina and the maintenance of vaginal eubiosis up to 30 days after the end of treatment, regardless of the route of administration ( 48 ). In contrast, a recent systematic review found that Lacticaseibacillus rhamnosus administered orally was more efficacious than intravaginal application for the treatment of BV ( 49 ), which was again likely to be due to unstandardized methodology mentioned above.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, the results should be interpreted cautiously as the number of studies included in the meta-regression analysis was rather limited ( k = 10). Similar to our results, a probiotic administration for a 10-day duration resulted in a significant reduction of pathogenic microbiota in vagina and the maintenance of vaginal eubiosis up to 30 days after the end of treatment, regardless of the route of administration ( 48 ). In contrast, a recent systematic review found that Lacticaseibacillus rhamnosus administered orally was more efficacious than intravaginal application for the treatment of BV ( 49 ), which was again likely to be due to unstandardized methodology mentioned above.…”
Section: Discussionsupporting
confidence: 90%
“…Hydrophobicity (H%), auto-aggregation (Auto-A%) and co-aggregation (Co%) abilities were tested as described by Pino et al (2021) [ 37 ]. Hydrophobicity was determined as bacterial adhesion to hydrocarbons (BATH) using xylene.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 71 presumptive G. vaginalis isolates (Supplementary Table 1) were recovered from the vagina of BV-positive patients enrolled at the Obstetrics and Gynecology Department, General Hospital G. Rodolico, University of Catania (Italy), and participated in a clinical trial approved by the local ethics committee (Comitato Etico Catania 1, Azienda Ospedaliero-Universitaria "Policlinico-Vittorio Emanuele" Catania, registration number 157/2019/PO; Pino et al, 2021). In detail, the vaginal…”
Section: Isolation and Identification Of Clinical Isolatesmentioning
confidence: 99%